2021
DOI: 10.3390/agronomy11091760
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Efficiency of Growth Regulators in Wheat under Drought Stress and Sandy Soil Conditions

Abstract: Drought stress and nutrient status are highly important for plant growth and productivity. Two field experiments were conducted during two consecutive seasons (2017–2018 and 2018–2019) at El-Molak, Abo-Hammad, Sharkia, Egypt. This work was conducted under sandy soil conditions to evaluate the effects of foliar application with growth regulators (PGRs) such as cycocel (CCC), applied at 0, 500, or 1000 mg L−1, and/or salicylic acid (SA), applied at 0, 0.05, or 0.1 mM on the productivity as well as improving drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Moreover, the application of PGPR increased the excretion of indole acetic acid (IAA) and bacterial exopolysaccharide from soil microbes, which is one of the main steps in the improvement of soil properties. by reducing the concentration of Na + , which antagonistically increases the phytoavailability of other nutrients, mainly K + , Ca 2+ , and Mg 2+ [ 31 ]. The application of PGPR, directly and indirectly, boosts the growth and development of plants growing under salinity stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the application of PGPR increased the excretion of indole acetic acid (IAA) and bacterial exopolysaccharide from soil microbes, which is one of the main steps in the improvement of soil properties. by reducing the concentration of Na + , which antagonistically increases the phytoavailability of other nutrients, mainly K + , Ca 2+ , and Mg 2+ [ 31 ]. The application of PGPR, directly and indirectly, boosts the growth and development of plants growing under salinity stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The potassium concentration of flag leaf and seed samples was determined according to Yoshida et al [20] using a flame photometer. The protein content of seeds was estimated after determining the concentration of nitrogen in the seeds and applying a coefficient of 6.25 [21].…”
Section: Plant Analysismentioning
confidence: 99%
“…Many researchers reported that shorter irrigation intervals improved the growth and yield traits of wheat crops (Shah et al, 2016;Ragheb et al, 2017;Ahmed and Mustafa, 2018;Walsh et al, 2020;Munsif et al, 2022). Increasing irrigation period was followed by a significant decrease in all studied traits except for protein under sandy soils conditions, which leads to rapid loss of water and nutrients, and exposes plants to drought stress, thus an increase in protein content of wheat plants (El-Saadony et al, 2021). Moreover, Awad et al (2015) illustrated that drought stress led to number of grains spike -1 by 28.58 and 28.74%, grain weight plant -1 by 17.97 and 39.60%, 1000-grain weight by 36.97 and 7.95%, and grain yield by 35.56 and 39.38%, in comparison to full irrigation treatment in both seasons, respectively.…”
Section: Effect Of Irrigation Intervalsmentioning
confidence: 97%